Hambatan yang Dihadapi Guru SD dalam Kenaikan Pangkat dengan Angka Kredit - Sunarso Sunarso (Universitas Negeri Malang, 2016)
This study is designed to know the problems faced by elementary school teachers to get a promotion by the credit points system, their abilities in doing activities evaluated by the system, and their suggestions on its implementation. The population is elementary school teachers in Depok, Sleman. A sample of 246 teachers is drawn randomly from the population. Data are collected by administering a questionnaire, and analyzed in percentages. The result shows that there are internal andexternal-bureaucratic problems faced by the teachers. According to the teachers, it is easy to teach, to guide their pupils, and to do other supportive activities. Professional development is supposed to be a difficult activity. They suggest that there must be a deregulation in promotion proposal and an automatic promotion system